A trust model for consumer conversion in community-based group buying: The dual roles of~group leaders - Huajing Ying; Huanhuan Ji; Xiaoran Shi; Xinyue Wang (Modern Supply Chain Research and Applications, 2022)
Purpose - In the presence of coronavirus disease 2019 (COVID-19), due to the social distance restriction, consumers' regular consumption behaviors and patterns have been changing fundamentally. Thereafter, an innovative group buying model has emerged and developed explosively with a specific focus on consumer's location, known as community-based group buying (CGB). The purpose of this paper is to investigate the transfer mechanism of user's trust in dyadic contexts of social and commercial role-playing in the CGB program. Design/methodology/approach - This study adopts an empirical research method, with an online and offline questionnaire survey, a total of 382 responses have been obtained. Then, both descriptive analysis and hierarchical regression analysis are conducted to explore the dual roles of group leader and its corresponding effects on consumers' trust (i.e. emotional trust and behavioral trust) and engagement actions (i.e. purchase and share) in the CGB program. Findings - Results indicate that resident's trust and their perception of group leader's friend role can positively enhance their engagement actions in the CGB programs. Meanwhile, for the purpose of profit maximization, the group leader is more willing to play a friend role in transactions no matter whether the role conflict exists. Originality/value - Research findings provide some managerial insights for CGB platform on the selection and training of group leaders and the incentive mechanism design.
Keywords: 650; Community-based group buying; Role theory; Social commerce; Trust theory